2008
DOI: 10.1530/eje-07-0853
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the humoral immune response to islet antigen 2 in children with newly diagnosed type 1 diabetes.

Abstract: Objective: To characterize the humoral immune response to islet antigen 2 (IA-2) in patients with newly diagnosed type 1 diabetes (T1D), we compared the profile of epitope-and isotype-specific IA-2 antibodies (IA-2A) between children with a humoral immune response restricted to IA-2 and children with a broad response including insulin autoantibodies (IAA) and antibodies to glutamic acid decarboxylase (GADA) in addition to IA-2A. Methods: The study subjects (nZ100) were derived from a consecutive series of 1108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
5
12
0
Order By: Relevance
“…Our observations that the appearance of IAA only tends to be associated with the HLA-DR4 haplotype while GADA only was associated with the HLA-DR3 haplotype is of considerable interest. Similar associations between HLA and islet autoantibodies have previously been observed at the time of clinical diagnosis [15, 16] extended to the observation that IA-2A was associated with HLA-DR4 but negatively associated with HLA-DR3 [15, 17]. The strong association between HLA and the seroconversion to a specific islet autoantibody therefore underscores prior observations that the association between HLA and type 1 diabetes at the time of clinical diagnosis are secondary to a primary association between HLA and an autoimmune response to either IAA only or GADA only.…”
Section: Discussionsupporting
confidence: 79%
“…Our observations that the appearance of IAA only tends to be associated with the HLA-DR4 haplotype while GADA only was associated with the HLA-DR3 haplotype is of considerable interest. Similar associations between HLA and islet autoantibodies have previously been observed at the time of clinical diagnosis [15, 16] extended to the observation that IA-2A was associated with HLA-DR4 but negatively associated with HLA-DR3 [15, 17]. The strong association between HLA and the seroconversion to a specific islet autoantibody therefore underscores prior observations that the association between HLA and type 1 diabetes at the time of clinical diagnosis are secondary to a primary association between HLA and an autoimmune response to either IAA only or GADA only.…”
Section: Discussionsupporting
confidence: 79%
“…Multinomial regression analysis revealed a positive association of the haplotype DRB1*040101/DQB1*0302 with altered anti-IA-2 titers in our population. These results are concordant with previous studies on Canadian (24), Japanese (20), German (10), Finnish (27,28), Italian (13), and Belgian (5) populations that showed that the prevalence and level of IA-2 autoantibody are increased in patients with HLA DR4/DQ8. However, IA-2 was negatively associated with DRB1*110101/ DQB1*030101 in titers and in prevalence.…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that the prevalence and increased titer of anti-GAD antibodies are associated with . This association between IA-2 and the DRB*04 allele was reported in previous studies (11,13,22,24). Multinomial regression analysis revealed a positive association of the haplotype DRB1*040101/DQB1*0302 with altered anti-IA-2 titers in our population.…”
Section: Discussionsupporting
confidence: 91%
“…The nationwide Finnish Pediatric Diabetes Register (27) has covered more than 90% of children diagnosed with T1D since June 2002 (28). By April 2007, the register had covered 1544 children who had T1D-related autoantibodies analyzed and were diagnosed with T1D before the age of 15 years.…”
Section: Study Design and Subjectsmentioning
confidence: 99%